Utilizing milk from pooling facilities as a novel approach for foot‐and‐mouth disease surveillance. Issue 4 (4th February 2020) - Armson, Bryony; Di Nardo, Antonello; Nyaguthii, Dickson M.; Sanz‐Bernardo, Beatriz; Kitala, Philip M.; Chepkwony, Eunice; Mioulet, Valerie; King, Donald P.; Lyons, Nicholas A.
Abstract: This study investigated the potential of pooled milk as an alternative sample type for foot‐and‐mouth disease (FMD) surveillance. Real‐time RT‐PCR (rRT‐PCR) results of pooled milk samples collected weekly from five pooling facilities in Nakuru County, Kenya, were compared with half‐month reports of household‐level incidence of FMD. These periodic cross‐sectional surveys of smallholder farmers were powered to detect a threshold household‐level FMD incidence of 2.5% and collected information on trends in milk production and sales. FMD virus (FMDV) RNA was detected in 9/219 milk samples, and using a type‐specific rRT‐PCR, serotype SAT 1 was identified in 3/9 of these positive samples, concurrent with confirmed outbreaks in the study area. Four milk samples were FMDV RNA‐positive during the half‐months when at least one farmer reported FMD; that is, the household‐level clinical incidence was above a threshold of 2.5%. Additionally, some milk samples were FMDV RNA‐positive when there were no reports of FMD by farmers. These results indicate that the pooled milk surveillance system can detect FMD household‐level incidence at a 2.5% threshold when up to 26% of farmers contributed milk to pooling facilities, but perhaps even at lower levels of infection (i.e., below 2.5%), or when conventional disease reporting systems fail. Further studies are required to establish a more precise correlation with estimates of household‐level clinical incidence, to fully evaluate the reliability of this approach. However, this pilot study highlights the potential use of this non‐invasive, routinely collected, cost‐effective surveillance tool, to address some of the existing limitations of traditional surveillance methods.